Financial accounting - Jennings, A.R (DP Publications, 1993)
Assumes a knowledge of the subject up to foundation level and equivalent. The book is designed to prepare students for professional and related examinations, such as ACCA, CIMA, AAT, ICSA, LCC, BTEC HNC/D, IComA and the practical aspects of the financial accounting content of degree courses.